Systematic review and classification of: Incredible Years Teacher school and kindergarten program (1. ed.) - Sørlie, Mari-Anne; Breivik, Kyrre (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2019)
Background: This paper is a systematic review of the universal Norwegian DUÅ school- and kindergarten program building on Webster-Strattonʼs indicated program IY-TCM (Incredible Years Teacher Classroom Management Training). The universal version is offered to personnel (max 25 persons per group) working with children aged 3-8 years in schools, after-school care and kindergartens mainly located in municipalities implementing the IY parent training program. The main goals of the school- and kindergarten program are to develop a common professional platform for structured efforts to promote childrenʼs mental health and to prevent conduct problems. Two group leaders lead the program training for six days during one school year, followed by supervision. The structured training focus on topics such as: 1) building positive relations, 2) reinforcement of positive behavior and coaching, 3) reward systems, 4) how to reduce problem behavior, 5) natural/arranged consequences, and 6) emotion regulation and problem-solving. The program owner is the regional Centre for Child and Youth mental health and Child Welfare – north Norway (RKBU-North), UiT The Artic University of Norway (Tromsø). Method: This review of research is based on systematic search for evidence in the national and international databases Embase, Medline, Psykinfo, NORART, Cochrane, Cristin, NORA, SCOPUS, SweMed, Bibsys, and Google Scholar. Information on the program was also collected from the program owner. Results: The review includes description of the intervention, effect studies, quality of research methods and implementation quality. The universal program has a solid theoretical foundation and a good description of the program components and training strategies are given. Two Norwegian quasi-experimental effectiveness studies based on teacher reports, published in four articles, were included in the review. The study results indicate that the program can reduce problem behavior and increase social competence among 3-8 years olds, and contribute to positive changes in student-teacher relationships and in parentsʼ involvement in school. In the total sample the short-term effect sizes were, however, small to marginal. The results indicate that the program has a more pronounced effect on reducing externalizing problems and student-teacher conflicts amongst high risk students. Within this group there was also found a moderate program effect on academic achievement. The internal validity of the evaluation results can be questioned. Per date, the program should not be described as school-wide, in that it is just implemented in 1st – 3rd grade. An implementation manual for schools and kindergartens and strategies for quality assurance are needed. Conclusion: The DUÅ school- and kindergarten program is classified at evidence level 4 – Program with satisfactory documentation of effect.